2009
DOI: 10.1111/j.1600-0706.2009.17362.x
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between abiotic stress and co‐occurrence patterns: an assessment at the community level using soil lichen communities and multiple stress gradients

Abstract: The stress‐gradient hypothesis (SGH) predicts a shift from predominant competition to facilitation as abiotic stress increases. Most empirical tests of the SGH have evaluated the interactions between a single or a few pairs of species, have not considered the effects of multiple stress factors, and have not explored these interactions at nested spatial scales. We sampled 63 0.25‐m2 plots, each subdivided into 100 5×5 cm and 25 10×10 cm sampling squares, in a semi‐arid Mediterranean environment to evaluate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 64 publications
5
36
0
2
Order By: Relevance
“…Callaway 2007). The results presented from Studies 1 and 4 are new re-analyses of previously published data (Maestre et al , 2009bMaestre & Escudero 2009). …”
Section: Methodssupporting
confidence: 63%
“…Callaway 2007). The results presented from Studies 1 and 4 are new re-analyses of previously published data (Maestre et al , 2009bMaestre & Escudero 2009). …”
Section: Methodssupporting
confidence: 63%
“…If we consider a matrix with taxa in rows, sites in columns, and abundances as entries, we maintained the richness of each row (i.e., row sums are fixed) and we set abundances among columns to be equiprobable (i.e., all sites had the same average number of entries) to build the null model (78). This fixed rows-equiprobable columns null distribution model retains taxa frequencies, i.e., rare taxa remain rare and common taxa remain common (79). The use of this null distribution model is recommended because it has a low probability of type I errors (78).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have dealt with small scale pattern formation of crusts. However, one study revealed a scale-dependent positive correlation between abiotic stress such as water and nutrient availability and co-occurrence of BSC-lichens (Maestre et al 2009). Büdel et al (2009) distinguished between 7 major crust types in their study on South African BSCs.…”
Section: Introductionmentioning
confidence: 99%